Weight loss over 48 months is associated with reduced progression of cartilage T2 relaxation time values: Data from the osteoarthritis initiative. Issue 5 (4th April 2014) - Serebrakian, Arman T.; Poulos, Theresa; Liebl, Hans; Joseph, Gabby B.; Lai, Andrew; Nevitt, Michael C.; Lynch, John A.; McCulloch, Charles E.; Link, Thomas M.
<x xml:space="preserve">Abstract</x> Purpose To assess whether changes in knee cartilage MR‐based T2 relaxation times are associated with weight loss in individuals with risk factors for knee osteoarthritis (OA) compared with controls with stable weight. Materials and Methods One hundred twenty‐seven individuals with risk factors for knee OA were studied: 62 subjects had a body mass index (BMI) decrease≥10% over 48 months and 65 controls had a BMI change <3%. Cartilage segmentation from five knee compartments at baseline and 48‐month follow‐up was performed, and T2 maps were generated. The association of change in T2 values over 48 months in the weight‐loss group versus the control group was assessed using multiple linear regression models. Results Weight loss was associated with significantly smaller increases in cartilage T2 in the medial femoral condyle (P = 0.035) and overall medial compartment (P = 0.006) compared with the controls. In a subgroup analysis comparing weight‐loss subjects who were obese (BMI≥30 kg/m2) and overweight (BMI 25–30 kg/m2) at baseline, obesity was associated with smaller increases in cartilage T2 values in the medial femoral condyle (P = 0.022), lateral femoral condyle (P = 0.015), patella (P = 0.002), and globally across all compartments (P = 0.002). Conclusion A decrease in BMI of ≥ 10% was associated with a slower progression of T2 values in individuals with risk factors for OA, suggesting a beneficial impact of weight loss on cartilage matrix degeneration. J. Magn. Reson. Imaging 2015;41:1272–1280. © 2014 Wiley Periodicals, Inc.